Water-soluble tomato concentrate modulates shear-induced platelet aggregation and blood flow in vitro and in vivo - Liu, Lu; Xiao, Shunli; Wang, Yilin; Wang, Yufang; Liu, Lei; Sun, Zhengxiao; Zhang, Qian; Yin, Xiaojie; Liao, Fulong; You, Yun; Zhang, Xuguang (Frontiers in Nutrition, 2022)
Water-soluble tomato concentrate (WSTC), extracted from mature tomatoes, is the first health product in Europe that has been approved "to help maintain normal platelet activity to maintain healthy blood flow". We hypothesized that WSTC might exert influence on blood flow shear stress-induced platelet aggregation (SIPA) and in turn maintain healthy blood flow. We used a microfluidic system to measure the effects of WSTC on SIPA in vitro, We also used the strenuous exercise rat model and the κ-carrageenan induced rat tail thrombosis model to demonstrate the effects of WSTC on blood flow. WSTC significantly inhibited platelet aggregation at pathological high shear rate of 4000 s-1 and 8000 s-1 in vitro (P < 0.05 or P < 0.01). WSTC reduced the platelet adhesion rate and increased the rolling speed of platelets by inhibiting binding to Von Willebrand Factor (P < 0.05 or P < 0.01). The oral administration of WSTC for 4 weeks in strenuous exercise rats alleviated hyper-reactivity of the platelets and led to a significant reduction in the plasma levels of catecholamine and IL-6. WSTC treatment also led to a reduction in tail length, reduced blood flow pulse index (PI) and vascular resistance index (RI) and ameliorated local microcirculation perfusion in a rat model of thrombosis. WSTC exerted obvious inhibitory effects on the platelet aggregation induced by shear flow and alleviated the blood flow and microcirculation abnormities induced by inflammatory reaction.